1973
DOI: 10.1042/bj1340821
|View full text |Cite
|
Sign up to set email alerts
|

Aberration of porphyrin metabolism in iron-deficient anaemic rats (Short Communication)

Abstract: Iron-deficient rats excreted greater amounts of 5-aminolaevulinate in urine but the output of porphobilinogen was decreased considerably. In addition, activity of the enzyme 5-aminolaevulinate dehydratase was diminished in bone marrow and liver. The results suggest that in iron deficiency a defect occurs in porphyrin synthesis at the level of porphobilinogen formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Thus, Kaneko [9] reported a de creased urinary excretion of this substance in 32 sideropenic cases. In contrast, Heilmeyer [7] in 16 sideropenic cases and Sharma [19] in a number of sideropenic mice found increased urinary ¿-ALA excretion. The observed disagreement in the results between various groups of in vestigators may be due to different methods used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Kaneko [9] reported a de creased urinary excretion of this substance in 32 sideropenic cases. In contrast, Heilmeyer [7] in 16 sideropenic cases and Sharma [19] in a number of sideropenic mice found increased urinary ¿-ALA excretion. The observed disagreement in the results between various groups of in vestigators may be due to different methods used.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Lichtman and Feldman [10] and Battistini et al [1] both in 9 cases had not found significant differences in comparison to normal controls. Furthermore, Sharma [19] noticed that the enzyme ac tivity in iron deficient rats was increased when expressed as units/ml packed red cells, whereas it remained unchanged when expressed as un its/ml of blood. This discrepancy in the results might be attributed to the lower haematocrit in iron deficient rats.…”
Section: Discussionmentioning
confidence: 99%